Dose‐response relationship of a new Timothy grass pollen allergoid in comparison with a 6‐grass pollen allergoid. Issue 11 (16th October 2017) - Pfaar, O.; Hohlfeld, J. M.; Al‐Kadah, B.; Hauswald, B.; Homey, B.; Hunzelmann, N.; Schliemann, S.; Velling, P.; Worm, M.; Klimek, L.
Summary: Background: Subcutaneous allergen immunotherapy with grass pollen allergoids has been proven to be effective and safe in the treatment of patients with allergic rhinoconjunctivitis. Based on the extensive cross‐reactivity among Pooideae species, it has been suggested that grass pollen extracts could be prepared from a single species, rather than from a multiple species mixture. Objective: To find the optimal dose of a Phleum pratense ( P. pratense ) allergoid preparation and compare its efficacy and safety to a 6‐grass pollen allergoid preparation. Methods: In this double‐blind, placebo‐controlled study (EudraCT: 2011‐000674‐58), three doses of P. pratense allergoid (1800 therapeutic units (TU), standard‐dose 6000 TU and 18 000 TU) were compared with placebo and the marketed 6‐grass pollen allergoid (6000 TU). In a pre‐seasonal dosing regimen, 102 patients were randomized to five treatment groups and received nine subcutaneous injections. The primary efficacy endpoint was the change in weal size (late‐phase reaction [LPR]) in response to the intracutaneous testing (ICT) before and after treatment, comparing the active allergoids to placebo. Secondary outcomes were the change in Total Nasal Symptom Score (TNSS) assessed in the allergen exposure chamber (AEC), the changes in P. pratense ‐serum‐specific IgG4 and the incidence of adverse events (AEs). Results: All three doses of the P. pratense and the 6‐grass pollen allergoid preparations were significantly superior to placebo for the primary outcome, whereas there were no significant differences in the change in TNSS. Compared to the standard‐dose, the high‐dose of P. pratense did not produce any additional significant benefit, but showed a slight increase in AEs. Yet this increase in AEs was lower than for the 6‐grass pollen preparation. Conclusions & Clinical relevance: The standard‐dose of the new P. pratense allergoid was comparable to the marketed 6‐grass pollen preparation at equal dose for the parameters measured.